2019
DOI: 10.35940/ijitee.i8221.078919
|View full text |Cite
|
Sign up to set email alerts
|

Digital Leadership Among School Leaders in Malaysia

Abstract: In line with the rapid development of IR 4.0, school leaders need to seize the opportunity to transform them by integrating technology in leadership style. Hence, this study is aimed at developing a measurement model and identifying the functions and behaviors of the digital leadership of the school leaders. Using the SEM AMOS analysis, a questionnaire collected from 352 primary and secondary school principals.The confirmatory factor analysis (CFA) was carried out in ascertaining the proposed factor. The findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 6 publications
(8 reference statements)
0
28
1
4
Order By: Relevance
“…Principals who establish professional improvement practices among teachers can increase teachers' confidence to integrate digital teaching and learning. However, Yusof et al (2019) found that the functions of the digital learning space have not yet reached the minimum requirements -which shows that, in Malaysia, principals have not yet been able to fully implement the constructs of digital leadership. This indicates that the principal needs to the gaps that still exist in his management and administration.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Principals who establish professional improvement practices among teachers can increase teachers' confidence to integrate digital teaching and learning. However, Yusof et al (2019) found that the functions of the digital learning space have not yet reached the minimum requirements -which shows that, in Malaysia, principals have not yet been able to fully implement the constructs of digital leadership. This indicates that the principal needs to the gaps that still exist in his management and administration.…”
Section: Discussionmentioning
confidence: 97%
“…The Malaysian Ministry of Education (MOE) has produced the ICT Transformation Plan 2019-2023, which was launched to support the digital education agenda in Malaysia (Ministry of Education Malaysia, 2019). Principals are required to train themselves to master digital technology skills, including the possession of digital technology-focused leadership characteristics (Yusof, Yaakob, & Ibrahim, 2019). Teachers are also encouraged to master ICT and digital technology competencies so as not to experience difficulties in implementing these changes (Tomte, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Principals who establish professional improvement practices among teachers can increase teachers' confidence to integrate digital teaching and learning. However, Yusof et al (2019) found that the function of digital learning space has not yet reached the minimum requirements which indicates that, in Malaysia, principals have not been able to fully implement digital leadership development in their management and administration.…”
Section: To Identify the Challenges Faced In Implementing Instruction...mentioning
confidence: 99%
“…Kementerian Pendidikan Malaysia (KPM) telah menghasilkan Pelan Transformasi ICT 2019-2023, yang dilancarkan untuk menyokong agenda pendidikan digital di Malaysia (Kementerian Pendidikan Malaysia, 2015). Pentadbir sekolah digesa untuk menguasai kemahiran teknologi digital, termasuk memiliki ciri kepimpinan yang berfokus kepada teknologi digital (Yusof et al, 2019). Para guru juga digalakkan untuk menguasai kemahiran teknologi digital agar tidak mengalami kesukaran dalam melaksanakannya perubahan pendidikan (N. H. Hamzah et al, 2021).…”
Section: Pengenalanunclassified